Challenges of Internally Displaced Persons (IDPs) and the Interventions in the Ashrayan-2 Project (Journal of Bangladesh Institute of Planners, 2025)
The escalating frequency of riverbank erosion in Bangladesh has led to a marked increase in the number of internally displaced persons (IDPs) who are deprived of essential services such  as  adequate  housing,  employment,  healthcare,  and  security.  In  response,  various interventions  have  been  implemented  by  government  bodies,  private sectors, and non - governmental  organizations  to  mitigate  the  impacts  of  displacement.  A  notable  recent initiative is the countrywide Ashrayan-2 project, targeting the rehabilitation of the landless- homeless people with a vision to uplift their livelihoods. As a representative sample of those eligible for resettlement, the IDPs' challenges are examined in this study, followed by an assessment  of interventions  in  the  Ashrayan  Project  in  a  riverbank  erosion  context. Employing Participatory Rural Appraisal (PRA) techniques and the Sustainable Livelihoods Framework (SLF), this qualitative research shows the issues that the Ashrayan-2 project addressed  and  those  that  were  not.  The  findings  of  this  study  offer  insights  and recommendations for future interventions and resettlement project design , considering the needs and challenges of IDPs and current project beneficiaries.JBIP, Vol. 17, 2024, pp. 101-118